Comparative Effects of Coenzyme Q10 or n-3 Polyunsaturated Fatty Acid Supplementation on Retinal Angiogenesis in a Rat Model of Oxygen-Induced Retinopathy - Kay D. Beharry; Charles L. Cai; Faisal Siddiqui; Sara Chowdhury; Christina D'Agrosa; Gloria B. Valencia; Jacob V. Aranda (MDPI AG, 2018)
Neonatal intermittent hypoxia (IH) or apnea afflicts 70% to 90% of all preterm infants <28 weeks gestation, and is associated with severe retinopathy of prematurity (ROP). We tested the hypotheses that coenzyme Q10 (CoQ10) or omega-3 polyunsaturated fatty acids (n-3 PUFAs) supplementation during neonatal IH reduces the severity of oxygen-induced retinopathy (OIR). Newborn rats were exposed to two IH paradigms: (1) 50% O2 with brief hypoxia (12% O2); or (2) 21% O2 with brief hypoxia, until postnatal day 14 (P14), during which they received daily oral CoQ10 in olive oil, n-3 PUFAs in fish oil, or olive oil only and compared to room air (RA) treated groups. Pups were examined at P14, or placed in RA until P21. Retinal angiogenesis, histopathology, and morphometry were determined. Both IH paradigms produced severe OIR, but these were worsened with 50/12% O2 IH. CoQ10 and n-3 PUFAs reduced the severity of OIR, as well as ocular growth factors in both IH paradigms, but CoQ10 was more effective in 50/12% O2 IH. Supplementation with either CoQ10 or n-3 PUFAs targeting IH-induced retinal injury is individually effective for ameliorating specific characteristics consistent with ROP. Given the complexity of ROP, further studies are needed to determine whether combined CoQ10 and n-3 PUFAs supplementation would optimize their efficacy and result in a better outcome.